Computational art experiments for the university: revealing culture, community and social spaces. Issue 2 (4th May 2019) - Giacobone, Gian Andrea; Camellina, Lorella
ABSTRACT: Universities are social entities that produce cultural and narrative environments. They are made up of people whose daily activities create datasets in the form of raw data, concealing information about their origins. We are often unaware of this flow of potential information as it is usually intangible, unexpressed and hence unutilized. To highlight and reveal this hidden quantity of data, there are many contemporary tools and specific digital data-mining processes at our disposal. This paper presents two experimental concepts resulting from a course at the University of San Marino Design School, located in the Santa Chiara monastery, in the City of San Marino. The two works explore the physical building through two different datasets characterizing the institution. They focus on revealing the invisible behaviours related to the social life of the University. To do this, two different dimensions have been considered, virtual space and physical space.